KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DAN KETERAMPILAN MENULIS TEKS PROSEDUR - Asriati, Maharani Dwi Putri; Gani, Erizal (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT The purpose of this study is three. First, describing reading skills understanding the procedural text of class VII students at SMP Negeri 25 Padang. Second, describing the procedure for writing the text skills of Grade VII students in Padang Middle School 25 Third, describing the correlation of reading skills in the text comprehension procedure and the procedure for writing text skills for grade VII students of SMP Negeri 25 Padang. This type of research is quantitative with descriptive method. The design used is correlational design. The study population was grade VII students of SMP Negeri 25 Padang who were enrolled in the 2018/2019 school year, which was 241 students. The study sample was determined by proportional random sampling of 20% of the population, namely 45 students. The research data is in the form of a reading skill test score understanding of the procedure text and the score of the procedure for writing the text procedure. There are two instruments for this research, namely objective tests to measure reading skills, comprehension of text procedures and performance tests to measure the procedure for writing text skills. text comprehension procedures, and procedure writing skills in class VII students of SMP Negeri 25 Padang. at the real level (α) of 95% with n-1 freedom degrees in other words if the reading skills of students 'procedural text comprehension are good, then students' writing skills are also good. Conversely, if the reading skills of students 'procedural text comprehension are bad then the students' writing procedure text skills are also bad. Kata kunci : keterampilan membaca pemahaman, keterampilan menulis                    teks prosedur